Digital economy and e-commerce: what has the comprehensive and progressive trans-pacific partnership agreement has to offer to Malaysia? - Abdul Ghani Azmi, Ida Madieha; Chun Phuoc, Jeong (2018)
The Malaysian government has introduced a number of flagship initiatives to leverage on digital economy and tapped the economic trade benefits it promises to the country. For digital economy to grow to its utmost potentials, a supportive eco-legal system is warranted, both at domestic level and international level. As at the heart of digital economy is speedy access to Internet as well as latest gadgets, applications and data analytics, facilitating transfer of data from one country to another should be a matter of first priority. Whilst government seeks to achieve that domestically by introducing relevant laws and regulations, it is no surprise that international norms on data transfer is equally imperative. Using doctrinal analysis, this article explores the position of data transfer in the E-Commerce Chapter of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) and compares that) existing domestic legal obligations. The E-Commerce chapter that contains provisions on spam, digital privacy, computer crimes, forced localizations and cross border data flow, are in some ways in requires enhancement of existing legal obligation. The paper concludes by suggesting that as free flow of data is instrumental to digital trade, the implementation of the E-Commerce Chapter would better serve the interests of the internet users generally and Malaysian digital economy specifically.